Sosialisasi Panduan Elektronis Pembelajaran Tajwid Berbasis Macromedia Flash (Tempat : Pondok Pesantren Modern Islam Assalaam Surakarta) - Rakhmadi, Aris; Kurniawan, Ady Purna (WARTA, 2010)
The purpose of this research is to develop and test an electronic learning system asan alternative learning media to read Al-Qurâan. The creation of this learning systemhas through some steps. The steps are references searching, data collecting, systematic creating, and testing. This process involves data collecting from tajwid books and video recording. The capacity of this system is 179 MB including 1.655 files consisting of 1 .exe file. 769 .swf files, 734 .flv video files, 151 mp3 files, and 3 folders. The resulted video has an extention .flv which has a size as big as 250 x 180 pixel. Frame Rate 15 fps, and Bit Rate 260 kbps. The resulted audio extents mp3 that has a Bit Rate 128 kbps, stereo channel and resolusion 16 bit. The questioners that are devided to the 20 users show that this programm is better and completer than tajwid books sold.